Prion disease resembling frontotemporal dementia and parkinsonism linked to chromosome 17 - Nitrini Ricardo; Silva Luís Sidônio Teixeira da; Rosemberg Sérgio; Caramelli Paulo; Carrilho Paulo Eduardo Mestrinelli; Iughetti Paula; Passos-Bueno Maria Rita; Zatz Mayana; Albrecht Stephen; LeBlanc Andrea (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare the clinical features of a familial prion disease with those of frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17). BACKGROUND: Prion diseases are not usually considered in the differential diagnosis of FTDP-17, since familial Creutzfeldt-Jakob disease (CJD), the most common inherited prion disease, often manifests as a rapidly progressive dementia. Conversely, FTDP-17 usually has an insidious onset in the fifth decade, with abnormal behavior and parkinsonian features. METHOD: We present the clinical features of 12 patients from a family with CJD associated with a point mutation at codon 183 of the prion protein gene. RESULTS: The mean age at onset was 44.0 ± 3.7; the duration of the symptoms until death ranged from two to nine years. Behavioral disturbances were the predominant presenting symptoms. Nine patients were first seen by psychiatrists. Eight patients manifested parkinsonian signs. CONCLUSION: These clinical features bear a considerable resemblance to those described in FTDP-17.